Representation and receiving it at Abdul-Qaher Al-Jarjani (Numerus academy review, 2026)
Representation by 'Abd al-Qaher al-Jarjani' is a special way to represent themeaning, it can have a special effect on the recipient, as the representation paraphrasesthe meaning sensually depends on photography, and through that, Abd al-Qaher al-Jarjanitried to build a difference in the effect that the recipient made if he received the meaning Just a photographer at the same time.